PERSEPSI PERNIKAHAN BAGI DEWASA DINI DARI KELUARGA KEKERASAN DALAM RUMAH TANGGA (KDRT) - marpaung, winida (Psychology Department Faculty of Psychology Universitas Medan Area, 2016)
Domestic violence give effect to early adulthood about marriage. This study used a qualitative approach with in-depth interviews and observation. Respondents amounted to three people, with criteria premature adults who come from families that experienced domestic violence. The results showed that every subject perceives marriage in different ways according to the parents marriage experience. Overview subject first wanted to marry and intend to do the same thing as her parents, the second subject consider that as the wife of the fair to receive treatment coarse husband, and a third subject assumes that he will do differently from perikahan parents and he wanted to know the couple before marriage so there is no domestic violence.